Callogorgia lucaya sp. nov., a new species of deep-sea Primnoidae (Anthozoa: Octocorallia) from the western Atlantic - Cordeiro, Ralf T. S.; Bayer, Frederick M.; Cairns, Stephen D. (Zootaxa, 2018)
As part of an ongoing reassessment of the genus Callogorgia, we describe C. lucaya sp. nov. from the western Atlantic, with a distribution so far restricted to the Straits of Florida and northern Caribbean. The species was partially described in an unfinished manuscript of Dr. Frederick Bayer and differs from all other western Atlantic species by commonly lacking outer-lateral body wall scales, having a small number of abaxials, and having body wall sclerites that are externally almost smooth. (Species Zoobank LSID: urn:lsid:zoobank.org:act:CF8F92FC-8F8A-4A8C-AF4A-52E12B58F7B1)